If I had a thousand lives - Broomhall, Anthony James, 1911-1994; China Inland Mission; Overseas Missionary Fellowship (London, UK Hodder and Stoughton, 1982)
Includes index.
Keywords: Taylor, James Hudson, -- 1832-1905.; Missions -- China -- History -- 19th century -- biography